Changes in CD73, CD39 and CD26 expression on T-lymphocytes of ANCA-associated vasculitis patients suggest impairment in adenosine generation and turn-over - Kling, Simon Lovis; Benck, Urs Tobias; Breedijk, Annette; Leikeim, Lisa; Porubský, Štefan; Krämer, Bernhard; Yard, Benito A.; Kälsch, Anna-Isabelle (Scientific reports, 2017)
Extracellular adenosine, generated via the concerted action of CD39 and CD73, contributes to T-cell differentiation and function. Adenosine concentrations are furthermore influenced by adenosine deaminase binding protein CD26. Because aberrant T-cell phenotypes had been reported in anti-neutrophil cytoplasmic auto-antibody (ANCA)-associated vasculitis (AAV) patients, an impaired expression of these molecules on T-cells of AAV patients was hypothesized in the present study. While in AAV patients (n = 29) CD26 was increased on CD4+ lymphocytes, CD39 and CD73 were generally reduced on patients’ T-cells. In CD4+ cells significant differences in CD73 expression were confined to memory CD45RA- cells, while in CD4- lymphocytes differences were significant in both naïve CD45RA+ and memory CD45RA- cells. The percentage of CD4-CD73+ cells correlated with micro-RNA (miR)−31 expression, a putative regulator of factor inhibiting hypoxia-inducible factor 1 alpha (FIH-1), inversely with serum C-reactive protein (CRP) and positively with estimated glomerular filtration rate (eGFR). No correlation with disease activity, duration, and ANCA profile was found. It remains to be assessed if a decreased CD73 and CD39 expression underlies functional impairment of lymphocytes in AAV patients. Likewise, the relations between frequencies of CD4-CD73+ cells and serum CRP or eGFR require further functional elucidation.